Frequency and Associated Factors of Severe Acute Malnutrition in Children Aged 6 to 59 Months in District Qambar Shahdadkot, Sindh - Kifayat Ali; Syed Muhammad Zulfiqar Hyder Naqvi; Nazia Jameel (Liaquat National Journal of Primary Care)
Background: Acute malnutrition is a serious public health problem reaching to epidemic proportions in certain regions of the world. It has been reported that children with severe malnutrition have weakened immunity and are prone to developmental delays, with a higher mortality risk from common childhood illnesses such as diarrhea, pneumonia and malaria. Objective: To determine the frequency and associated factors of severe acute malnutrition in children aged 6-59 months at District Headquarter Hospital, Qambar Shahdadkot, Sindh. Methods: A cross-sectional study was conducted from November 2021 to February 2023 among children aged 6-59 months at District Headquarter Hospital, District Qamber Shahdadkot, Sindh, Pakistan. Data were collected by means of interviews using the study questionnaire. Height was measured using a height board (Stadio Meter), weight was measured using SECA digital weighting scale while mid upper arm circumference was measured using MUAC tape. Data were analyzed by SPSS version 20. Crude and adjusted odd ratios with 95% confidence interval were computed using binary logistic regression to determine the association of socio-demographic characteristics with the nutritional status of children. Results: The study results showed that the mean age of study children was 26.58±14.54 months, 101 (50.5%) of them were less than 2 years old, 109 (54.5%) were male, 149 (74.5%) were exclusively breastfed for 6 months, only 19 (9.5%) of them started weaning between the age of 4 to 6 months and 147 (73.5%) were completely immunized. Moreover, 26 (13.0%) of them had severe acute malnutrition. On the multivariable model, only child age was found to be significantly associated with the nutritional status of children (aOR: 4.07, 95% CI 1.14-14.48, p=0.030). Conclusion: Among the study sample, 13% of children had severe acute malnutrition. Moreover, among the socio-demographic characteristics studied, only the age of child was found to be significantly associated with the nutritional status of a child.